Fecal microbiota transplantation modulates gut microbiota and lipid metabolism to reduce diarrhea in low-birth-weight neonatal calves - Zhang, Zhanhe; You, Duo; Wu, Donglin; Li, Xintong; Jia, Yang; Harmon, David L.; Xu, Ming (Frontiers in Animal Science, 2026)
This study aimed to elucidate the mechanism by which colonic fecal microbiota transplantation (FMT) improves lipid metabolism in low-birth-weight neonatal calves via modulation of the gut microbial ecosystem. In a completely randomized design, seventy newborn Holstein calves (1 day old, 32.63 ± 3.13 kg BW) were assigned to two groups (35 calves/treatment; 30 females and 5 males per group). A healthy calf was used as a fecal donor. A 10% fecal bacterial suspension was prepared and administered colonically (50 mL, twice daily for 5 days). All calves were fed the same milk replacer and weaned using a step-down protocol at 60 days of age. Blood samples were collected from the jugular vein on days 1, 7, and 14. Six calves near the group average body weight were selected from each treatment group for serum, fecal microbial, and serum metabolomic analyses. Fecal samples collected on day 7 were subjected to 16S rRNA sequencing (V3–V4 regions) for microbiota profiling. Serum metabolites were analyzed using LC–MS/MS with Progenesis QI 2.3. The results showed that FMT improved growth performance, reduced the incidence and duration of diarrhea, and significantly decreased serum total cholesterol. These changes were associated with a reduction in the abundance of Ruminococcus_gnavus_group, a genus positively correlated with serum total cholesterol. Metabolic pathway analysis revealed that two lipid-related pathways—glycerophospholipid metabolism and ether lipid metabolism—were altered in the FMT group compared to the control. In conclusion, FMT reduces diarrhea and enhances host health by modulating the gut microbial ecosystem to improve lipid metabolism in neonatal calves.